Utilization of Used Goods as Learning Media to Increase Students' Creativity at UPTD SDN 1 Anjatan Utara, Anjatan District, Indramayu Regency - Aden Yusuf Zakaria; Lesy Luzyawati; Anilia Ratnasari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Natural Science (IPA) is an important learning in elementary schools. IPA is knowledge related to natural phenomena, not only a collection of facts and concepts, but also about how to work, how to think, and how to solve problems. Natural science is also interpreted as knowledge about nature obtained based on human experience due to interaction with its environment. Problems that often arise in learning the content of IPA material include the lack of availability of learning media, teaching and learning activities using more lecture methods, students' attention is less focused on the provision of material by the teacher. To realize meaningful IPA learning, learning media are needed. Learning media are all tools that can be used to achieve educational goals. Learning media have a very important function in learning activities, both for teachers and students. Learning media will make learning more interesting, can provide meaningful learning experiences, activate and please children and the existence of learning media will provide motivation in the learning process. Examples of learning media that can be applied to science learning are learning media that utilize used goods. Learning media from used goods is an interesting and creative alternative to make the teaching and learning process more effective and enjoyable. by using items available in the surrounding environment, especially used goods such as cardboard, bottled drinking water, paper, straws, etc. In addition, the use of used goods can also help foster a sense of love for the environment in children. Learning media from used goods can make the teaching and learning process more interesting and enjoyable, so that it can increase children's interest in learning. Utilizing used goods to make learning media can help develop children's creativity. Playing with learning media from used goods can help train children's motor skills. Utilizing used goods to make learning media can help foster a sense of love for the environment in children. Therefore, we students who are doing KKN 2024 in Anjatan Utara Village, Anjatan District took the initiative to apply learning media from used goods to increase students' creativity and awareness of the environment.